2014
DOI: 10.1016/j.cegh.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Burgeoning double burden of tuberculosis and diabetes in India: Magnitude of the problem – Strategies and solutions

Abstract: Background: India reportedly has a fifth of tuberculosis burden worldwide. There is a strong epidemiological evidence for an association between tuberculosis and diabetes mellitus (DM). Patients with diabetes are at increased risk of developing active TB, and have higher rates of treatment failure and death, even when placed on appropriate therapy. Objective: We sought to perform a comprehensive review of the convergence of these two epidemics in India and strategies for co-management. Methods: We performed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Such a collaboration presents an opportunity for a comprehensive and integrated approach to address diabetes and TB, two leading public health challenges in China. Standard treatment guidelines which incorporate the core issues in the bidirectional screening and cost‐effective management of TB and diabetes need to be developed and enforced . Screening can be conducted in those with T2DM to maximise the cost‐effectiveness of TB screening, especially young cases with poorly controlled glucose levels and low body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Such a collaboration presents an opportunity for a comprehensive and integrated approach to address diabetes and TB, two leading public health challenges in China. Standard treatment guidelines which incorporate the core issues in the bidirectional screening and cost‐effective management of TB and diabetes need to be developed and enforced . Screening can be conducted in those with T2DM to maximise the cost‐effectiveness of TB screening, especially young cases with poorly controlled glucose levels and low body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Although not identified in this research, an article published in India showed that collaboration is also hindered due to patients with TB being largely managed in public health facilities, as compared with patients with DM, who are mostly being cared for in private health facilities. 122 …”
Section: Discussionmentioning
confidence: 99%
“…One of the major findings was lack of awareness on TB/DM co-infection or coexistence. Correspondingly, a study carried out in India by Sharm et al, WHO [16,25,22] also identified lack of awareness as a major element for hindered integration and growth of TB-DM integrated clinical services.…”
Section: Discussionmentioning
confidence: 99%